'A Tale of Two Sibleys': ceramic counter narratives, globalization, individuality and the last century of the Ely pottery industry c. 1770–1870. (4th May 2019) - Cessford, Craig
Abstract : SUMMARY: Pottery production at Ely, Cambridgeshire, began in the 11th–12th centuries and continued until around 1864, but the 18th–19th century industry has largely been ignored. By considering the later stages of the industry, the issue of why the Ely pottery industry ended when it did will be considered at scales from the intimate and personal to broader ceramic globalization. This also demonstrates why British archaeologists need to pay more attention to Modern vernacular ceramics.